Concentration in the fertilizer industry - Leconte-Demarsy, Delphine (2023)
Delphine Leconte-Demarsy IFPRI-AMIS SEMINAR SERIES Market Concentration in the Grain Industry: Implications for Food Security? Co-organized by IFPRI and Agricultural Market Information System (AMIS) SEP 7, 2023 - 9:30 TO 11:00AM EDT